Cam teach and prosper? EFL teachers’ attitudes, well-being, and coping strategies in an online setting - Martinović Anna; Dumančić Dino (ExELL (Explorations in English Language and Linguistics))
The global Covid-19 pandemic led to the turn toward online learning and the need to adapt to new ways of English foreign language (EFL) teaching. This mixed-methods research aimed to examine teacher attitudes, well-being, and coping strategies related to online EFL teaching. The results indicated that Croatian EFL teachers had a positive attitude toward online teaching and acknowledged the importance of being digitally competent. EFL teachers were unsure about their ability to deal with online teaching and indicated their need to improve their IT skills. They revealed more negative than positive responses regarding their well-being and showed that they tried to actively cope during the pandemic. Results also showed better coping strategies among female teachers.